2013
DOI: 10.1007/s00395-013-0376-7
|View full text |Cite
|
Sign up to set email alerts
|

Pre-conditioning with synthetic CpG-oligonucleotides attenuates myocardial ischemia/reperfusion injury via IL-10 up-regulation

Abstract: The aim of the study was to investigate whether pre-conditioning with CpG-oligodeoxynucleotides (CpG-ODN) may change cardiac ischemia/reperfusion (I/R)-dependent inflammation and modulates infarct size and cardiac performance. WT and TLR9-deficient mice were pre-treated with 1668-, 1612- and H154-thioate or D-Gal as control. Priming with 1668-thioate significantly induced inflammatory mediators in the serum and a concomitant increase of immune cells in the blood and spleen of WT mice. Furthermore, it induced m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
44
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 48 publications
2
44
0
2
Order By: Relevance
“…Velten et al () demonstrated that CpG‐ODN 1668 treatment attenuates cardiac hypertrophy following pressure overload by modifying the inflammatory response, thereby reducing cardiac growth and fibrosis as well as delaying the loss of cardiac function. Moreover, it has also been reported that the TLR9 activation induced by CpG‐ODN attenuates myocardial ischemia/reperfusion injury (Cao et al, ; Markowski et al, ). However, TLR9‐stimulation upon the onset of ischemia and subsequent reperfusion does not provide any benefit for cardiac ischemia/reperfusion injury (Ohm, Gao, et al, 2014).…”
Section: Introductionmentioning
confidence: 97%
“…Velten et al () demonstrated that CpG‐ODN 1668 treatment attenuates cardiac hypertrophy following pressure overload by modifying the inflammatory response, thereby reducing cardiac growth and fibrosis as well as delaying the loss of cardiac function. Moreover, it has also been reported that the TLR9 activation induced by CpG‐ODN attenuates myocardial ischemia/reperfusion injury (Cao et al, ; Markowski et al, ). However, TLR9‐stimulation upon the onset of ischemia and subsequent reperfusion does not provide any benefit for cardiac ischemia/reperfusion injury (Ohm, Gao, et al, 2014).…”
Section: Introductionmentioning
confidence: 97%
“…Pharmacological preconditioning, however, may offer greater translational potential as dosages are easily controlled. We, and others, have demonstrated that pharmacological preconditioning via Toll-like receptor 9 (TLR9) holds great promise for use in prophylactic protection of the brain [12-14] as well as other organs against ischemic injury [15, 16]. …”
Section: Introductionmentioning
confidence: 99%
“…TLR9 mediated protection against ischemic injury, to date, has only been demonstrated with B-class CpGs [12-16], and although the protection is robust, increased systemic cytokine levels may restrict their use as clinical therapeutics. The A-class CpGs, with their minimal induction of systemic cytokines, may provide a safer alternative for prophylactic protection if, despite their distinct immune modulation, they protect against ischemic injury.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported a benefit of CpG-ODN in sepsis and cardiac function after I/R [12][13][14][15]. However, recent studies have demonstrated that TLR9 could be a therapeutic target for reducing myocardial I/R injury.…”
mentioning
confidence: 99%